Corporate governance practices and liquidity management: special reference of selected manufacturing companies listed on the colombo stock exchange - Velnampy, T.; Nimalathasan, B.; Kalaiarasi, K. (university of Jaffna, 2014)
This paper examines the relation between corporate governance practicesand liquidity management. Hence good corporate governance practicesoptimize the liquidity management and long term value of the firm for shareholders. There is a great awareness among the researchers to carry out the researches in “liquidity management'. Very little researches on “liquidity management” are available in Sri Lanka and need to be empowered companies to pay a special attention on corporate governance. The main objective of this study is to examine the relationship between corporate governance practicesand liquidity managementin listed manufacturing firms in Sri Lanka. Design:In a way, the present study is initiated on “corporate governance practicesand liquidity management“with the samples of 20 manufacturing companies using the data representing the periods of 2008 2012. The statistical tests were used includes: descriptive statistics, correlation and regression analyses. Findings: The study found that determinants of corporate governance are not correlated to the liquidity managementmeasures of the organization. Regression model showed that corporate governance don't affect companies' CR, and QR. Further recommendations are also put forwarded in the research. Research Limitations: The study only used data from the 2008-2012 annual reports. However, the findings have highlighted the effects of the liquidity managementand corporate governance. Originality/Value: The study contributes to literature in Sri Lanka. Furthermore, the finding of the paper can be considered as helpful for managers and users that are anxious to develop financial description quality and practices of capital structure.
Keywords: Corporate governance; Liquidity management; Leadership structure; Board committee; Board meeting; Board size; Current ratio; Quick ratio; Manufacturing companies